The necessary international legal protection of historical, artistic and cultural heritage in Spanish private international law: Special attention to the case of Cassirer - Ortega Giménez, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
In a globalised world, cultural heritage is fundamental for the identity and collective memory of a society, and its preservation is a shared objective between different societies. This paper analyses the importance of the international legal protection of historical, artistic and cultural heritage in the field of Spanish private international law, with a particular focus on the Cassirer case. This case involves a claim by the Cassirer family for the restitution of a painting of impressive cultural value, “Rue Saint-Honoré, après-midi, effet de pluie” by Camille Pissarro, which was looted by the Nazis during the Second World War. This study highlights the importance of international cooperation and legal harmonisation in the protection of cultural heritage, and provides practical examples of disputes over the restitution of works of art looted during historical conflicts, which pose complex legal challenges.
Keywords: Private international law; art-historical and cultural heritage; international legal protection; Cassirer case